Use of refractory bricks as sand replacement in self-compacting mortar. Issue 1 (1st January 2017) - Aboutaleb, Djamila; Safi, Brahim; Chahour, Kahina; Belaid, Amrane
Abstract: This present work investigate the possibility of using refractory bricks (RB) as fine aggregates (by partial and total substitution of natural sand) in self-compacting mortars (SMCs). For this, an experimental study was carried out to evaluate physical and mechanical properties ((bulk density, compressive and flexural strength) of the self-compacting mortars (SCMs) with partial and total substitution of natural sand (NS) by crushed refractory bricks (RB) at different ratio (BR/S = 0, 10, 30, 50 et 100%) by weight. The results obtained show that the RB (0/5 mm class), can be used as fine aggregates for self-compacting mortar, without affecting the essential properties of mortar. However, the performances of RB-based mortar (100% as sand), were better and are suitable for a fluid concrete (such as self-compacting concrete).